Molecular and Physiological Variability in Bread Wheat and Its Wild Relative (Aegilops tauschii Coss.) Species under Water-Deficit Stress Conditions - Zahra Khodadadi; Mansoor Omidi; Alireza Etminan; Asa Ebrahimi; Alireza Pour-Aboughadareh (BioTech, 2022)
Aegilops and Triticum spp. are two ideal gene pools for the breeding purposes of wheat. In this study, a set of Iranian accessions of Aegilops tauschii Coss. and Triticum aestivum L. species were evaluated in terms of some physiological and biochemical features under control and water-deficit stress conditions. Moreover, several simple sequence repeat (SSR) markers were employed to identify marker loci associated with the measured traits. The results indicated that water-deficit stress significantly affected all measured traits and the highest reductions due to water-deficit were recorded for shoot fresh and dry biomasses (SFB and SDB), stomatal conductance (Gs), leaf relative water content (RWC), and chlorophyll b content (Chl b). In molecular analysis, 25 SSR markers generated 50 fragments, out of which 49 fragments (98%) were polymorphic. Furthermore, the genetic variation observed within species is more than between species. The results of cluster and Bayesian model analysis classified all evaluated accessions into three main clusters. Under control and water-deficit stress conditions, 28 and 27 significant marker-trait associations (MTAs) were identified, respectively. Furthermore, 10 MTAs showed sufficiently stable expression across both growth conditions. Of these, the markers Xgwm-111, Xgwm-44, Xgwm-455, Xgwm-272, and Xgwm-292 were associated with multiple traits. Hence, these markers could serve as useful molecular tools for population characterization, gene tagging, and other molecular breeding studies.